The Impact of a Single Stretching Session on Running Performance and Running Economy: A Scoping Review - Konrad, Andreas; Močnik, Richard; Nakamura, Masatoshi; Sudi, Karl; Tilp, Markus (Frontiers in Physiology, 2021)
One determining factor for running performance is running economy,which can be quantified as the steady-state oxygen consumption at a given running speed.Stretching is frequently applied in sports practice and has been widely investigated in recent years However,the effect of stretching on running economy and performance is not clear.Thus,the purpose of this scoping review is to investigate the effects of a single bout of stretching on running economy and running performance in athletes(e.g. recreational and elites) and non-athletes.The online search was performed in the PubMed,Scopus,and Web of Science databases.Only studies that explored the acute effects of stretching on running economy(or similar variables) and/or running performance variables with healthy and adult participants independent of activity level were included in this review.Eleven studies met the inclusion criteria with a total of 44 parameters(14 performance related/30 metabolic parameters) and 111 participants.Regardless of the stretching technique, there was an improvement both in performance variables(21.4%) and metabolic variables(13.3%) following an acute bout of stretching.However, also detrimental effects in performance variables(28.5%) and metabolic variables(6.6%) were reported.Though, the results were influenced by the stretching duration and technique.Although it was observed that a single static stretching exercise with a duration up to 90 s per muscle group can lead to small improvements in running economy(1.0%;CI(95%):−1.04 to 2.22), negative effects were reported in running performance (−1.4%(CI(95%):−3.07 to −0.17). It was also observed that a single bout of dynamic stretching only resulted in negligible change in running economy −0.79% (CI(95%):−0.95 to 4.18) but in a large increase in running performance (9.8%(CI(95%):−3.28 to 16.78) with an overall stretch duration(including all muscles) between 217 s to 900 s.Therefore,if stretching is applied without additional warm-up, the results suggest applying dynamic stretching (for a short overall stretching duration of ≤220 s) rather than static stretching if the goal is to increase running performance.In general, only short static stretching durations of ≤60 s per muscle-tendon unit are advisable.One study reported that less-flexible runners have greater benefits from stretching than athletes with normal flexibility.In addition,it can be suggested that less-flexible runners should aim for an optimum amount of flexibility,which would likely result in a more economical run.